Factors Associated with Psychological Distress, Fear, and Coping Strategies during the COVID-19 Pandemic in Thailand: A Cross-Sectional Study - Patraporn Bhatarasakoon PhD, FAAN; Suwit Inthong MSN; Sirirat Nitayawan MSN; Ratree Thongyu PhD; Chayapa Sanlaung PhD; Muhammad Aziz Rahman MPH, PhD (SAGE Publishing, 2024)
Introduction Despite being initially perceived as a local infectious disease, COVID-19 has emerged as one of the most perilous global health threats, significantly impacting the psychological well-being of individuals worldwide. Objective This cross-sectional descriptive study investigates the psychological distress, fear, and coping mechanisms among Thai people residing in Thailand during the COVID-19 pandemic. Methods This online cross-sectional survey targeted Thai individuals during the first and third waves of the COVID-19 pandemic. Participants aged 18 and above who provided consent self-reported their responses to the Kessler Psychological Distress Scale, Fear of COVID-19 Scale, and Brief Resilient Coping Scale. Data collection occurred between November 2020 and January 2021 across four regions of Thailand. Univariate and multivariate logistic regression analyses explored associations between contextual factors and the variables of interest. Results Out of 498 survey respondents, with an average age of 43.07 (SD = 13.69) years, 81.9% were female, and 61.6% self-identified as healthcare workers, with 47.59% identified as frontline healthcare workers. Findings revealed that 46% of participants experienced moderate-to-very high levels of psychological distress, 14.3% reported high levels of fear of COVID-19, and 35.1% exhibited low resilient coping. Factors such as changes in employment status or financial situations, comorbidities, contact with known or suspected COVID-19 cases, recent healthcare utilization for COVID-19-related stress, and elevated fear of COVID-19 were associated with higher levels of psychological distress. Conversely, being nurses and perceived better mental health status were linked to more effective coping strategies. Conclusion These results emphasize the critical importance of government interventions to safeguard the psychological well-being of healthcare workers and the broader Thai population. Urgent measures to bolster resilience among these groups during and after the pandemic are imperative.